Analisa Pemanfaatan Teman Sebaya dalam Perkembangan Belajar Siswa Pada Program Keahlian di SMK PGRI 2 Kota Jambi - Redi Indra Yudha; Ulul Azmi; Lusi Larasati (Universitas Batanghari Jambi, 2020)
In this study it self will focus more on one extrinsic influence, namely peers. This is based on considerations that at SMK PGRI 2 Jambi City students have chosen their abilities in their own expertise program, while considerations such as environment and classroom management through the use of peer-to-peer approaches have not had much impact on their own learning development, both inside and outside school. Based on the results of descriptive analysis of research where the analysis is used to find out a description of each research variable used, the results obtained by using peer variables are in the good category with a total value of Respondents' Achievement of 81.64. This can indicate that in developing the ability to acquire skills in vocational learning, peer factors have an influence on students' understanding of learning. In the analysis results obtained in the Communalities table itself, it can be seen that the acquisition of the MSA value from the highest point is at P7 (community) of 0.730. Meanwhile, the lowest MSA value was at P2 (relative order) of 0.512. This explains that the student community in group learning plays an active role in improving the abilities and skills of vocational students when carrying out teaching and learning activities both theoretical and practical.